Dynamics Research of Double Cross Universal Joints based on Rigid-flexible Coupling - Li Junhu; Wang Weibing; Lou Laifeng; Wang Yipeng (Jixie chuandong)
Based on the rigid-flexible coupled multi-body dynamics theory,with software of three-dimensional solid design,on the basis of finite element software and multi-body dynamics software,the coupled dynamics simulation model of double cross universal joints is created. The flexible characteristic of intermediate shaft hollow section is taken into consideration in this model. The mode analysis of intermediate shaft is carried out and modal neutral file is obtained. To study the influence of angle size that formed among input shaft with intermediate shaft and output shaft with intermediate shaft on transmission uniformity,the dynamics simulation analysis in three kinds of misalignment angle are carried out. The research results show that the less difference in angle size of input shaft between intermediate shaft and output shaft between intermediate shaft,the smaller inhomogeneity in the rotation,it is consistent with the universal joint transmission theory. The modeling and analysis method provides a reference way to design and optimize the cross universal joints.